A comparison of intact and degraded desmin in cooked and uncooked pork longissimus thoracis and their relationship to pork quality. (July 2017) - Richardson, E.; Bohrer, B.M.; Arkfeld, E.K.; Boler, D.D.; Dilger, A.C.
Abstract: The objective was to compare desmin abundance (intact, degraded, and the ratio of intact desmin to degraded desmin) in samples from cooked and uncooked pork and establish its relationship to pork quality traits. Pork chops (2.54-cm thick) from twenty-four pork loins were randomly assigned to treatment (cooked or uncooked). Intact and degraded desmin in cooked and uncooked chops aged 1 d were weakly correlated (r < | 0.35 |) with Warner-Bratzler shear force at 1 and 14 d postmortem aging. Intact and degraded desmin in cooked and uncooked chops aged 14 d were moderately correlated (| 0.35 | < r < | 0.59 |) with Warner-Bratzler shear force at 1 and 14 d postmortem aging. Intact:degraded desmin in cooked and uncooked pork aged 1 and 14 d was generally weakly correlated (r < | 0.35 |) with pork quality traits, with only a few exceptions. This research supports previous reports that the same sample can be used for tenderness of cooked pork and the determination of desmin abundance. Highlights: Intact and degraded desmin were compared between cooked and uncooked samples. Intact and degraded desmin are affected by post-mortem aging and cooking. Correlation of intact and degraded desmin with pork quality traits was evaluated. Correlation coefficients were roughly similar in cooked and uncooked samples. One sample is sufficient for cooked pork evaluation and desmin determination.